Survey of Satisfaction on the 2022 National Pomnas Badminton Competition in Padang, West Sumatra - Amiranda, Aldo Ganang; Darmawan, Arief; Kurniawan, Rama (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2023)
Sports event management is very important to support the successful implementation of sporting events. The purpose of this study was to evaluate the implementation of the 2022 POMNAS XVII badminton competition in Padang, West Sumatra. The population of this study was badminton athletes with a total of 169 consisting of 95 boys and 74 girls. The sampling technique in this study used incidental sampling with a population of 63 athletes. Data collection techniques in this study used closed questionnaires. Data analysis used is descriptive quantitative analysis in which the data processing is presented in percentages. The results of the data analysis show that the percentage of services in the field of competition is 71.59%, services in the health/medical sector are 74.60%, services in the security sector are 71.74%. The results of this study indicate that the average service in this study is included in the good category but needs to be improved for several aspects of the field service.